Long-Term Trends in Ultra-Processed Food Consumption by Cardiometabolic Disease Status in the Framingham Offspring Study. (7th June 2021) - Juul, Filippa; Lin, Yong; Deierlein, Andrea; Vaidean, Georgeta; Parekh, Niyati
Abstract: Objectives: Ultra-processed foods currently provide the majority of calories in the U.S. and are closely linked with cardiometabolic diseases. Yet, little is known regarding consumption trends among individuals with and without cardiometabolic diseases. The current analyses examined longitudinal trends in diet processing level from 1991–2008 within the Framingham Heart Study Offspring Cohort by disease status. Methods: Analyses were conducted using dietary data serially collected by a food frequency questionnaire at study exams every 4 years between 1991–2008. The analytical sample included 2893 adults with valid dietary data for ≥3 exams (mean age: 54.0 y). Based on the NOVA framework, foods were classified as unprocessed/minimally processed foods, processed culinary ingredients (salt, sugar, fats and oils), culinary preparations (homemade baked goods and dishes), processed foods and ultra-processed foods. Consumption of each processing level (servings/d) were examined by calculating means, standard deviations and p-values for trends over the 4 exams. Mixed effects models with subject-specific random intercepts were used to account for within-subject correlation. Trends were stratified by prevalent cardiometabolic disease (CVD, diabetes, hypertension). Results: Among individuals with cardiometabolic diseases, over 17 years of follow-up, consumption of ultra-processed foods (7.9–6.1 servings/d) and minimally processed foods (11.2–10.6 servings/d) decreased (p-trend < 0.001). Intakes of processed foods, culinary ingredients and culinary preparations changed minimally during the study period. Trends were similar among individuals without cardiometabolic diseases (ultra-processed foods 7.3 to 5.8 servings/d) and minimally processed foods (11.3–11.0 servings/d) (p-trend < 0.001). Conclusions: Consumption of ultra-processed foods, a putative cardiovascular risk factor, remained high throughout the 1990s and 2000s, among aging adults, regardless of the cardiometabolic disease status. Yet, processing level has not been addressed in federal or clinical dietary guidelines. Future investigations should determine if dietary recommendations distinguishing ultra-processed from moderately and minimally processed foods facilitate healthier food choices. Funding Sources: None.